Increasing production of matrix metalloproteinases, tumor necrosis factor-Î±, vascular endothelial growth factor and prostaglandin E2 in rheumatoid arthritis synovial fibroblasts by different adiponectin isoforms in a concentration-dependent manner - Li, B T; Zhang, F Z; Xu, T S; Ding, R; Li, P (Cellular and Molecular Biology, 2015)
Adipokines have been known to play a significant role in rheumatic disease via synovial fibroblasts. However, to date, the concentration effects of adiponectin isoforms on the pathophysiology of rheumatoid arthritis (RA) have not been extensively studied. Therefore, the present study examined the different effects of the adiponectin isoforms on rheumatoid arthritis synovial fibroblasts (RASF) and investigated the relations between the concentration of individual adiponectin isoforms and the production of the inflammatory factors of RASF. Articular synovial tissues were obtained from the patients fulfilled with diagnostic criteria of RA, and health people. RASF and human fibroblast-like synoviocytes (HFLS) were isolated and cultured. They were stimulated with increasing concentrations of 25 Î¼g/ml, 50 Î¼g/ml, and 100Î¼g/ml of different human adiponectin isoforms. The levels of matrix metalloproteinase (MMP)-3, MMP-10, tumor necrosis factor (TNF)-Î±, vascular endothelial growth factor (VEGF), and prostaglandin E2 (PGE2) in culture supernatants were measured by immunoassays. The results showed the levels of MMP-3, MMP-10, TNF-Î±, VEGF and PGE2 were significantly increased in RASF which were treated with individual adiponectin isoforms compared to untreated RASF (p<0.01), and the increases also had significances compared to HFLS which were treated with the same conditions (p<0.05). Moreover, the effect of HMW (high molecular weight)/ MMW (middle molecular weight) was the strongest among them. In conclusion, all three adiponectin isoforms may contribute to proinflammatory effect by stimulating the production of MMP-3, MMP-10, TNF-Î±, VEGF and PGE2 of RASF in a concentration-dependent manner. HMW/MMW adiponectin could play an important role in matrix destroying and synovial vascular creating of the pathology of RA.